Analisis Profesionalisme Aparatur Sipil Negara di Daerah Otonomi Khusus - Sherwin Mikhael Soantahon (Ministry of Home Affairs, 2022)
The background of this study was the need to see the level of professionalism of the State Civil Apparatus (Aparatur Sipil Negara/ASN) in regions with Special Autonomy status. This need arose due to the many reports, findings, and results of studies that showed unprofessional ASN services in the Special Autonomy regions. Cases such as corruption, low quality of public services, and other complaints are some examples of cases of the many unprofessional cases in the Special Autonomy regions. This study aimed to look at the level of professionalism of ASN who were serving in Special Autonomy provinces during the time of the study, such as Aceh, Papua, and West Papua. The purpose of this study was to see the level of ASN professionalism in those provinces. The method used was a quantitative approach with data collection techniques using data processing documentation excavation techniques. The professional level was measured from the ASN Professionality Index (ASN PI), as issued by the National Civil Service Agency (Badan Kepegawaian Negara/BKN), and the level of leadership competence, which was based on the participation of High-Ranking Officials (JPT) in National Leadership Training (PKN) issued by the State Administration Agency (Lembaga Administrasi Negara/LAN). This study found that the level of ASN professionalism in the Special Autonomy provinces was not good. Of the two variables in this study, only the competency development variable showed good results. However, the professionalism variable did not show similar results. This result was in line with the results of several previous studies and reports or facts on the field. The unprofessionalism of ASN in the Special Autonomy provinces has caused many issues. Based on the results of this study, it is recommended that the ASN in the Special Autonomy regions be given special attention to foster and improve their professionalism and competence to enable the improvement of the public services in the Special Autonomy regions.